2021
DOI: 10.1002/ajoc.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Alkynylazulenes as Building Blocks for Highly Unsaturated Scaffolds

Abstract: Recently developed routes to the synthesis of mono‐ and polyethynylated azulenes and their transformations into linear oligoazulenes with ethynyl and butadiynyl bridges as well as azulenyl‐substituted benzenes, cyclobutadiene complexes, and azulene‐substituted tetracyanobutadienes are reviewed. The utility of ethynylazulene derivatives for the synthesis of azulene‐substituted heterocycles has also been reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 216 publications
0
4
0
Order By: Relevance
“…Furthermore, the reactivity of mono‐ and poly[(azulenyl)ethynyl]benzene derivatives to [2 + 2] cycloaddition/cycloreversion reactions with TCNE and TCNQ resulted in buta‐1,3‐dienes as a new class of charge‐transfer chromophores. [ 9 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the reactivity of mono‐ and poly[(azulenyl)ethynyl]benzene derivatives to [2 + 2] cycloaddition/cycloreversion reactions with TCNE and TCNQ resulted in buta‐1,3‐dienes as a new class of charge‐transfer chromophores. [ 9 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
“…Furthermore, the reactivity of mono-and poly[(azulenyl)ethynyl]benzene derivatives to [2 + 2] cycloaddition/cycloreversion reactions with TCNE and TCNQ resulted in buta-1,3-dienes as a new class of charge-transfer chromophores. [9] Pd-catalyzed cross-coupling under Sonogashira conditions, Corey-Fuchs or Seyferth-Gilbert reaction [119] for the conversion of aldehydes into acetylenes, or the reaction of chloroazulenes with lithium acetylide in liquid ammonia all result in efficient ethynylation of azulene at the five-membered or seven-membered ring. Jarszak-Tyl et al [120] recently reported solvent-free C H alkynylation of azulenes via simple mortar grinding of substrates with aluminum oxide.…”
Section: Gold Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…8 These substituted acenes are also attracting attention because of their ability to absorb visible light, which enables them to be used as photoreduction catalysts. 9,10 Furthermore, azulene [11][12][13][14][15][16][17][18][19][20] is a structural isomer of naphthalene, with relatively high HOMO and low LUMO energy levels due to its unique polarisation structure (Fig. 1a), and it is also known as a redox-active molecule compared to naphthalene, anthracene, pyrene and so on.…”
mentioning
confidence: 99%